Expression of two "immediate early" genes, Egr-1 and c-fos, in response to renal ischemia and during compensatory renal hypertrophy in mice. - Ouellette, A J (1990)
To identify specific genetic regulatory mechanisms associated with renal ischemia, we measured the accumulation of Egr-1 and c-fos mRNAs in the mouse kidney after occlusion of the renal artery and reperfusion. At 1 h after right nephrectomy and arterial occlusion of the contralateral kidney for 10 or 30 min, Egr-1 mRNA levels were three to five times greater in these kidneys as compared with those in control animals that had sustained unilateral nephrectomy alone and were much greater than levels in the normal organ. Whether ischemia was imposed for 10 or for 30 min, renal Egr-1 mRNA contents were equivalent and remained elevated after 24 h of reperfusion subsequent to 30 min of ischemia. Although c-fos mRNA also accumulated in response to ischemia and reperfusion, the pattern differed from that of Egr-1 in that c-fos mRNA content varied with the duration of ischemia and was undetectable 24 h after injury. Contralateral nephrectomy was not necessary to see the marked accumulation of Egr-1 and c-fos mRNAs with unilateral ischemia. Reflow was necessary, however, since only minimal sequence accumulation occurred by the end of the ischemic period. After left uninephrectomy alone, Egr-1 mRNA levels in the remaining kidney were maximal 30 min after surgery, but were not detectable thereafter; c-fos mRNA levels did not change after unilateral nephrectomy. Differential expression of early growth-related genes implicated in transcriptional activation may influence tissue recovery after renal ischemia.